Performance of clay masonry veneer in wood-stud walls subjected to out-of-plane seismic loads. - Okail, Hussein O.
This paper presents the findings of shaking-table experiments conducted to examine the out-of-plane seismic performance of masonry veneer walls. Seven wall assemblies were tested, each consisting of a clay masonry veneer anchored to a wood-stud backing. Design variables include the type of veneer ties, tie spacing, and presence or absence of mortar joint reinforcement and window opening. The walls were designed and constructed in accordance with current US code provisions. Results of the experiments show that failure of the corrugated ties is governed by pullout of the nails from the wood studs, while failure of the rigid ties is governed by detachment from the mortar joints or pull-through of the screw heads through fastener holes. Both types of ties show satisfactory performance under ground motions corresponding to Design Basis and Maximum Considered Earthquakes representative of Seismic Design Category E. Although the rigid ties were stronger than the corrugated ties, they had wider vertical spacing and failed at a slightly higher seismic load. Observed extraction capacities of the nails show high variability, which merits attention. Joint reinforcement did not show any noticeable effect on the out-of-plane behavior of the veneer. Results of an analytical study have shown that the detachment of a veneer from the backing system is preceded by veneer cracking, which influences the distribution of tie forces, and that the vertical tie spacing influences the cracking load for the veneer.
Keywords: Seismic performance; Shaking-table tests; Masonry; Veneer; Brick; Anchors; Wood frames; Corrugated ties; Rigid ties; Joint reinforcement